2015
DOI: 10.1021/acs.est.5b01228
|View full text |Cite
|
Sign up to set email alerts
|

The Depths of Hydraulic Fracturing and Accompanying Water Use Across the United States

Abstract: Reports highlight the safety of hydraulic fracturing for drinking water if it occurs "many hundreds of meters to kilometers underground". To our knowledge, however, no comprehensive analysis of hydraulic fracturing depths exists. Based on fracturing depths and water use for ∼44,000 wells reported between 2010 and 2013, the average fracturing depth across the United States was 8300 ft (∼2500 m). Many wells (6900; 16%) were fractured less than a mile from the surface, and 2600 wells (6%) were fractured above 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…The amount of separation between potable groundwater resources and drilling, stimulation and operation of wells associated with oil and gas activities is a critical consideration in oil and gas producing regions [13,40]. The required separation between unconventional oil and gas production and water wells in the USA is likely on the order of several hundred meters [41]. Analysis of several unconventional oil and gas plays indicated that only 1% of fractures propagate to distances of 350 m or more [42].…”
Section: Vertical Separation Of Water Wells and Hydrocarbon Productionmentioning
confidence: 99%
“…The amount of separation between potable groundwater resources and drilling, stimulation and operation of wells associated with oil and gas activities is a critical consideration in oil and gas producing regions [13,40]. The required separation between unconventional oil and gas production and water wells in the USA is likely on the order of several hundred meters [41]. Analysis of several unconventional oil and gas plays indicated that only 1% of fractures propagate to distances of 350 m or more [42].…”
Section: Vertical Separation Of Water Wells and Hydrocarbon Productionmentioning
confidence: 99%
“…S1. Fluid injections into deeper formations, such as water disposal and waterflooding for enhanced oil/gas recovery, are ongoing and will continue to occur in California (54,55). In addition, geologic storage of CO 2 (56,57) …”
Section: Central Valleymentioning
confidence: 99%
“…Understanding potential contamination pathways and sources is essential for protecting groundwater resources. Baseline data are essential for attributing groundwater contamination to specific anthropogenic activities such as oil and gas production [41] and waste disposal but is often lacking [42]. Deep groundwater is already used in the US, and, more commonly, in Mexico and other arid regions around the world.…”
Section: Discussionmentioning
confidence: 99%